Правовые основы государственной власти в Испании - Соколова Ольга Владимировна (Норма, 2016)
Экземпляры: СЭ (20160525) / Инвентарный номер: 1098356 / Цена: / Сис.шифр: 67.400 / Авт.знак: С 59 / ГРНТИ: 10 / ББК: 67.400(4Исп)